Freezing-thawing-resistant solidified sludge soil and preparation method thereof - KE RUI; ZUO QINGJUN; WANG HONGXING; TAN YUNZHI; WU JUN; HUANG LONGBO; MING HUAJUN (2017)
Freezing-thawing-resistant solidified sludge soil is prepared from, by weight, 100 parts of sludge, 5-15 parts of cement, 0-5 parts of quick lime and 0.0-5 parts of bentonite, wherein the sludge is acquired from a field and can be obtained after branches, tree leaves and the like in the sludge are removed without other pretreatment, the bentonite is sodium bentonite, and the alkaline coefficient of the sodium bentonite is greater than 1. By adopting the freezing-thawing-resistant solidified sludge soil and a preparation method of the soil, the problems of difficult sludge dewatering and high aggregate cost can be solved, the instant mechanical property of the solidified sludge soil can be effectively improved, meanwhile the degradation effect of the freezing-thawing cycling effect on the solidified sludge soil is inhibited, and the safety performance of solidified sludge soil filling construction is improved. 种抗冻融固化淤泥土，它包括下述重量份配比的组份：淤泥100；水泥5-15；生石灰0-5；膨润土0.5-5；其中，淤泥为现场采集获得的淤泥，取出其中的树枝、树叶等杂物即可，不需要进行其他的预处理；膨润土为